The value of a marginal change in capacity at congested airports. (August 2018) - Adler, Nicole; Yazhemsky, Ekaterina
Abstract: We assess the value of a marginal change in the number of slots at congested airports from the perspective of the different stakeholders including airports, airlines and passengers. We analyze the trade-off between the benefits, in the form of revenues for airlines and airports as well as greater variety for passengers and the costs that arise from delays. Utilizing a non-parametric structural equation modeling approach, we compare a set of US airports with their first-come first-served policy to those of Europe in which slots are allocated according to grandfather rights. Delays in Europe are much lower than their US counterparts, suggesting that regulation in Europe could be relaxed leading to increased movements and relatively minor increases in delays hence higher overall social welfare. Perhaps surprisingly, we also find that the introduction of slots in the US (or reduction in slots allocated at the four currently constrained airports) would not necessarily increase overall social welfare. In summation, European regulation prevents optimal use of current infrastructure whereas the US system is better able to capitalize on their existing infrastructure.